Characterization of a rotary piezoelectric energy harvester based on plucking excitation for knee-joint wearable applications - Pozzi, Michele; Zhu, Meiling (Institute of Physics (IOP), 2012)
Wearable medical and electronic devices demand a similarly wearable electrical power supply. Human-based piezoelectric energy harvesters may be the solution, but the mismatch between the typical frequencies of human activities and the optimal operating frequencies of piezoelectric generators calls for the implementation of a frequency up-conversion technique. A rotary piezoelectric energy harvester designed to be attached to the knee-joint is here implemented and characterized. The wearable harvester is based on the plucking method of frequency up-conversion, where a piezoelectric bimorph is deflected by a plectrum and permitted to vibrate unhindered upon release. Experiments were conducted to characterize the energy produced by the rotary piezoelectric energy harvester with different electric loads and different excitation speeds, covering the range between 0.1 and 1 rev s −1 to simulate human gait speeds. The electrical loads were connected to the generator either directly or through a rectifying bridge, as would be found in most power management circuits. The focus of the paper is to study the capability of energy generation of the harvester for knee-joint wearable applications, and study the effects of the different loads and different excitation speeds. It is found that the energy harvested is around 160–490 {µJ} and strongly depends on the angular speed, the connected electric loads and also the manufacturing quality of the harvester. Statistical analysis is used to predict the potential energy production of a harvester manufactured to tighter tolerances than the one presented here.